Predictors of brand referral behaviors of cosmetic brand among gen-Y consumers - Noor Hasaniyati, Mohd Rejab (2018)
The purpose of this study is to examine the relationship between brand knowledge, brand personality, brand experience and brand referral behaviors among Gen-Y in context of cosmetic brand among UUM undergraduate business students. In total, 350 questionnaires were distributed to UUM School of Business Management (SBM) undergraduate students. However, only 338 questionnaires were returned and only 335 questionnaires were usable for further analysis. The data collected through this survey was analyzed by using the Statistical Package for Social Science (SPSS) version 23. This study used random sampling method which includes both proportionate sampling and systematic sampling. Proportionate sampling is to identify adequate and relevant number of sample for each program under SBM and systematic sampling specifically to choose the right respondent. The descriptive analysis was used to determine the respondent’s profile. Findings of this study revealed that brand knowledge has a positive significant relationship towards brand referral behaviors. Meanwhile, it was found that brand personality and brand experience has no significant relationship towards brand referral behaviors. This study will help managers and marketers to understand more deeply about brand referral behaviors among Gen-Y. Finally, this study proposes several recommendations for future research.